Information System for Payment of Dues and Savings at SMA Negeri 1 Cibungbulang School Based on WEB - Kamilah, Nurul; Munajir, Kayum; Fajri, Hersanto (Ilmu Komputer, FMIPA, Universitas Pakuan, 2024)
SMA Negeri 1 Cibungbulang, in recording Student Dues and Savings, still uses a spreadsheet application, where transaction recording use spreadsheet application has identified four cases that were complained of by the school administration: first, when recording payment transaction data, there was still an error in data input; secondly, when created the recapitulation report is still less effective and efficient; third when entering the school year the school Administration needs to re-create spreadsheet pages to separate old and new data; fourth transaction data is still prone to be scattered due to manual storage. Because of this, we need a better alternative to managing student finances so that it can be more effective and efficient. This study aims to analyze, design, and build a WEB-based Information System for Student Dues and Savings at SMA Negeri 1 Cibungbulang. The results obtained can improve the performance of the school administration in managing school finances. The system development method used is the waterfall model, which consists of four steps: Requirement Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing. The results of this study obtained an information system that can manage information consisting of student data, class data, monthly dues data, savings, and recapitulation reports with automatically generate recapitulation reports also present a user-friendly user interface design so that errors in payment input and calculating the number of months in one semester do not occur. This information system is aimed at School Treasurer Staff, School Treasurer, and the Principal.